Verruca Vulgaris and Seborrheic Keratosis Exacerbated by Immunosuppression - Shohei Iida; Kyoko Sugioka; Makoto Kondo; Yoshiaki Matsushima; Kento Mizutani; Koji Habe; Keiichi Yamanaka (Case Reports in Dermatological Medicine)
Verruca vulgaris is an infectious disease caused by the human papillomavirus and characterized by hyperkeratotic papules or plaques with a clear boundary. Seborrheic keratosis is a commonly encountered lesion on the face, trunk, or extremities and is described as seborrheic verruca because of its clinical similarity to warts; furthermore, it is occasionally associated with immune suppression, especially in cases of Leser-trélat syndrome. Although these diseases are frequently found in healthy individuals, they typically show a good response to cryotherapy. However, cases in immunosuppressed patients are intractable to therapy. Overall immune status is evaluated via complete blood count (CBC); however, white blood count does not show the exact immune ability, and NK cell activity is often decreased in cases of malignancy. Here, we present two cases of exacerbated verruca vulgaris and seborrheic verruca observed in patients with malignancy. Although the patients seemed to be in good condition and had a normal CBC, immunosuppression was suspected based on the degree of skin rashes. NK cell activity was decreased in both patients, and both cases had malignancy. The measurement of NK cell activity may be a useful approach to evaluate immune status.